HUBUNGAN ANTARA MINAT MENULIS DENGAN PENGUASAAN PERANTI KOHESI DAN KOHERENSI DALAM PEMBELAJARAN BAHASA INDONESIA PADA SISWA KELAS X SMK SEKOTA SUKABUMI TAHUN PELAJARAN 2016/2017 (CORRELATION BETWEEN THE INTEREST IN WRITING AND THE MASTERY OF COHESION AND COHERENCE TOOLS IN INDONESIAN LANGUAGE LEARNING OF CLASS X VOCATIONAL HIGH SCHOOL IN SUKABUMI CITY) - Faizal Arvianto; deden ahmad supendi; Tanti Agustiani (Balai Bahasa Jawa Barat, 2018)
This study aims to determine whether or not the relationship between interest in writing with the mastery of tools of cohesion and coherence in learning Indonesian language in the students of class X SMK Se-Kota Sukabumi. Interest is a great desire for something. Interests can affect the quality of student learning outcomes in accordance with the particular field of study. This makes researchers interested in conducting research on the relationship between interest in writing with the mastery of tools of cohesion and coherence considering the tools of cohesion and coherence is an important part in the formation of discourse. This study is devoted to the interest in writing and mastery of cohesion and coherence tools in Indonesian language learning, because in Indonesian language learning writing skills and tools of cohesion and coherence are widely studied. This research uses quantitative research method with correlational approach. The researcher collected data with questionnaire instruments for interest data of menuls and multiple choice test instruments for cohesion and coherency tool mastery data. Determination of the sample using random sampling technique because the sampling was chosen randomly without considering the strata in the population. Data analysis technique used product moment correlation technique with 5% significance level. Based on the results of data analysis revealed that interest in writing students average-average 74.8% and well-categorized. Mastery of cohesion tools and student coherence averaging 70% of good categorized. Based on the results of data analysis of each variable stated that there is a positive relationship between the interest of writing with the mastery of tools of cohesion and coherence in students of class X SMK Se-Kota Sukabumi in learning Indonesian language lesson 2016/2017. From the calculation results there is a correlation of 0.290 and included in the correlation coefficient of low category. From the results of t-test significance, there is a score of t count of 3.248> from the table t score of 1.980. So it can be concluded that there is a positive and significant relationship between the interest of writing with the mastery of tools of cohesion and coherence in the students of class X SMK Se-Kota Sukabumi academic year 2016/2017.